An application regarding the availability of mind maps in visual art education based on active learning method - (:unkn) unknown (ELSEVIER SCIENCE BV, 2015)
This study is conducted in order to inquire about the availability of mind maps in Visual Arts Education lessons which are performed based on active learning methods. It's applied on 3nd grade students taking course of Special Education Methods lesson in Marmara University Ataturk Education Faculty Fine Arts Education Department. 20 students who have similar success averages are selected from 40 people classroom as 10 of them for group control and 10 of them for experimental group. Traditional method is applied to control group and active learning method is applied to experimental group. At the end of the course, mind maps are applied as a final test on both groups. In this research, content analysis and semi-experimental methods are used. The mind maps are finalized by coding, students' opinions are taken. (C) 2015 The Authors. Published by Ltd.
Keywords: Visual Arts Education; Mind Map; Active Learning Method